ON DYNAMIC MODELLING OF COMPRESSED AIR ENGINE WITH CONNECTING- ROD-CRANK TO CONTROL ANGULAR POSITION OF OSCILLATING ROTATION - Alves, Alexandre C. [UNESP]; Balthazar, Jose M. [UNESP]; Tusset, Angelo M.; Rocha, Rodrigo T. [UNESP]; Bueno, Atila M. [UNESP]; ASME (Amer Soc Mechanical Engineers, 2017)
In this work is examined the dynamic behavior and the controllability of a compressed air engine with a connecting rod-crank. The pneumatic motor is composed by a mono cylinder, a connecting-rod and a control crank to the oscillating rotation. For the obtainment the nonlinear mathematical model was considered the Lagrange's method and the components of the physical system in the model are considered as rigid bodies with unilateral restriction. Numerical analysis of the application of the passive control position by a nonconservative pneumatic force with pilot valves in the cylinder showed that it was not possible an exact control to the angular position desired for the output crank. To solve this problem, it is proposed an active control by the Linear Quadratic Regulator method (LQR), to the control of the connecting-rod-crank mechanism. In addition, the robustness of the proposed control technique is tested considering noise measurement in pneumatic external excitation. The numerical simulation results showed the efficiency of the proposed control to the nonlinear dynamic model of the connecting-rod-crank and the sensibility analysis for parametric errors to the control of the oscillating angular positions, demonstrating so that the proposed active control is adequate for this system.